2002
DOI: 10.1128/ec.1.6.936-943.2002
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HSP90 in Trypanosoma cruzi Induces a Stress Response but No Stage Differentiation

Abstract: The 90-kDa heat shock proteins (HSP90) are important in the regulation of numerous intracellular processes in eukaryotic cells. In particular, HSP90 has been shown to be involved in the control of the cellular differentiation of the protozoan parasite Leishmania donovani. We investigated the role of HSP90 in the related parasite Trypanosoma cruzi by inhibiting its function using geldanamycin (GA). GA induced a dose-dependent increase in heat shock protein levels and a dose-dependent arrest of proliferation. Ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 33 publications
2
48
0
1
Order By: Relevance
“…In Leishmania donovani, Hsp90 plays a key role in the differentiation of the promastigote stage to the pathogenic mammalian amastigote stage (31). Hsp90 is also implicated in the development and survival of other intracellular parasites, such as Eimeria tenella (53), Toxoplasma gondii (54), and Trypanosoma cruzi (55). Hsp90 was found to be essential in the filarial nematode Brugia pahangi; exposure of B. pahangi to geldanamycin, a specific inhibitor of Hsp90, killed adult worms and microfilariae in vitro (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…In Leishmania donovani, Hsp90 plays a key role in the differentiation of the promastigote stage to the pathogenic mammalian amastigote stage (31). Hsp90 is also implicated in the development and survival of other intracellular parasites, such as Eimeria tenella (53), Toxoplasma gondii (54), and Trypanosoma cruzi (55). Hsp90 was found to be essential in the filarial nematode Brugia pahangi; exposure of B. pahangi to geldanamycin, a specific inhibitor of Hsp90, killed adult worms and microfilariae in vitro (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…The HSP90 protein family comprises evolutionarily conserved abundant cytosolic proteins that have been involved in chaperone function, oncogenic transformation, cell cycle control, and antigen presentation. This family also functions in the structural folding and maintenance of the conformational integrity of various proteins, including several cellular signal transduction proteins (Csemely et al 1998;Byrd et al 1999;Graefe et al 2002;Prodromou and Pearl 2003;Tsutsumi and Neckers 2007;Hao et al 2010). HSP90 is also required for normal spermatogenesis, oogenesis, and embryogenesis in Drosophila spp.…”
Section: Introductionmentioning
confidence: 99%
“…Hsp90 function is, thus, critical for survival of T. brucei. In other systems, inhibition of Hsp90 function by GA causes proteotoxic stress, which induces expression of various heat shock proteins (Wiesgigi and Clos 2001;Graefe et al 2002;Kamal et al 2004). We found that GA treatment also induces the level of Hsp90 protein in both the procyclic and the bloodstream forms (Fig.…”
Section: Resultsmentioning
confidence: 64%